Antenna design and implementation patch diamond array 2x4 elements with DGS shaped dumbbell square head at frequency 2.4 GHz - Koesmarijanto Koesmarijanto; Sania Ahva Y; Hendro Darmono (Politeknik Negeri Malang, 2023)
— Technological advances in the field of telecommunications without cables or wireless are growing rapidly by utilizing radio waves as transmission. This happens because people's mobility is currently quite high and requires practicality in the use of devices. The discussion in this paper is about the comparison of the design and fabrication performance of a diamond microstrip patch antenna composed of a 2x4 element array using DGS and without using DGS. The design was carried out using the CST 2018 simulator. The DGS was placed on a PCB ground plane with an epoxy fiberglass substrate having a dielectric constant of 4.58. This is measured by improving the value of VSWR, return loss, and bandwidth. The application of the working frequency used by the microstrip antenna is at (2401-2495) MHz for WIFI (Wireless Fidelity) networks. Microstrip antennas have a narrow bandwidth shortage, so they require bandwidth widening using the DGS (Defected Ground Structure) technique in the form of dumbbell square ahead. The resulting bandwidth is 15 MHz wider than a microstrip antenna without DGS. This research is in accordance with the antenna test parameters, which have a return loss value of -24.3dB, VSWR 1.12 and a bandwidth of 34 MHz.